Risk Factors for Foot Amputation in Patients Hospitalized for Diabetic Foot Infection - Maria Teresa Verrone Quilici; Fernando de Sá Del Fiol; Alexandre Eduardo Franzin Vieira; Maria Inês Toledo (Journal of Diabetes Research)
The aim of this study was to identify and quantify risk factors for amputation in diabetic patients hospitalized for foot infections. This cross-sectional study comprised 100 patients with diabetic infectious complications in the lower limbs. The variables investigated were related to diabetes, infection, and treatment compliance. Multiple Cox regression analysis was performed to identify the variables independently associated with the outcome of amputation. The most prevalent chronic complications were neuropathy and hypertension. Most patients presented with a neuroischemic foot (86%). The Morisky test showed that 72% were not compliant with diabetes treatment. Regarding patient outcome, 61% progressed to amputation, 14% to debridement, and 9% to revascularization. The results showed a 42% higher risk for progression to amputation in patients with previous use of antimicrobials. Also, the amputation risk was 26% higher for those less compliant with diabetes treatment. An increase of one point in the Wagner ulcer classification criteria corresponded to a 65% increase in the risk of amputation. Undergoing conservative, nonsurgical procedures prior to admission provided a 63% reduction in the risk of amputation. Knowledge of these factors is critical to enable multidisciplinary teams to develop treatment plans for these patients so as to prevent the need for amputation.